2016
DOI: 10.15376/biores.12.1.912-922
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional Stability and Mechanical Properties of Plantation Poplar Wood Esterified Using Acetic Anhydride

Abstract: Plantation poplar (Populus ussuriensis) wood was esterified using acetic anhydride without catalysts to improve its dimensional stability. The effects of acetylation temperature (100 °C, 120 °C, and 140 °C) on the dimensional stability, mechanical properties, microstructure, and functional groups of the resulting acetylated wood were systematically investigated. Results showed that the wood acetylated at 100 °C and 120 °C had an improved dimensional stability and comparable mechanical properties to those of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
4
10
0
Order By: Relevance
“…Even though T4 had minimum WPG of 23.94 ± 0.87%, it showed an insignificant difference in ASE with respect to T1 and T2. The ASE for T4 was comparable with the result obtained by CHAI et al 2017 for Populus ussuriensis wood modified with acetic anhydride and heated without chemical at 120 °C. It was from 74.13±0.61% to 55.71 ± 0.36%, ASE for T1 was 69.82 ± 0.87% to 55.28 ± 0.13% (Figure 6).…”
Section: Dimensional Stabilitysupporting
confidence: 84%
See 1 more Smart Citation
“…Even though T4 had minimum WPG of 23.94 ± 0.87%, it showed an insignificant difference in ASE with respect to T1 and T2. The ASE for T4 was comparable with the result obtained by CHAI et al 2017 for Populus ussuriensis wood modified with acetic anhydride and heated without chemical at 120 °C. It was from 74.13±0.61% to 55.71 ± 0.36%, ASE for T1 was 69.82 ± 0.87% to 55.28 ± 0.13% (Figure 6).…”
Section: Dimensional Stabilitysupporting
confidence: 84%
“…Ear-lier study showed the WPG of 20-25% in Southern pine specimens using a xylene and acetic anhydride mixture without catalyst with similar treatment conditions like those of T3 (Rowell 1982). The WPG of 19.7% observed for T4 was higher than that of Populus ussuriensis for acetic anhydride modification when heated without chemical at 120 °C (Chai et al 2017). It was also reported that the upper limit of WPG (30%) due to acetylation is irrespective of the reaction time.…”
Section: Weight Percent Gain Percentage Volume Increase Volumetric Swelling Coefficient Due To Chemical Treatmentmentioning
confidence: 89%
“…This decrease in stiffness is in line with the results of previous studies, which link the observed decrease in stiffness to the presence of acetic acid in wood as by-product of acetylation. The acid could induce hydrolysis of carbohydrate polymers during and after treatment (Dreher 1964;Chai et al 2016). Possible hydrolysis of cellulose may lead to a decrease in stiffness as cellulose represents the main stress-bearing polymer of the cw due to its very high stiffness compared to the cw matrix (Winandy and Rowell 1984).…”
Section: Impact Of Acetylation On Mechanical Propertiesmentioning
confidence: 99%
“…On the other hand, some mixed reviews have been proposed for the reactivity of the hydroxyl group in cellulose that all hydroxyl groups participate and convert into cellulose acetate. [51][52][53][54][55]…”
Section: Gibbs Free Energy Calculationsmentioning
confidence: 99%